Integrating socially accountable health professional education and learning health systems to transform community health and health systems - Brianne Wood; Michael Fitzgerald; Claire Kendall; Erin Cameron (Wiley, 2021)
Abstract A learning health system aims to create value in health systems using data‐driven innovations, quality improvement techniques, and collaborations between health system partners. Although the concept is mobilized through cycles of learning, most instantiations of the learning health system overlook the importance of formalized learning in educational settings. Social accountability in health professional education focuses on measurably improving people's health and health care, specifically through education and training activities. In this commentary, we argue that the idea of social accountability clearly articulates a rationale and a broad range of aspirations, whereas the learning health system offers an approach to achieve these goals. With a similar aim to a learning health system, social accountability promotes partnerships between health professional education, the health system, and communities in a way that allows for co‐designed and contextualized interventions. On the other hand, learning health systems prioritize data, research, and analytic capacities to facilitate quality improvement. An integrative framework could enhance learning cycles by collectively designing interventions and innovations with people and communities from health, research, and education systems. As well as aspiring to improve population health and health equity, such a framework will consider broader impacts, including the degree of participation amongst a range of partners and the level of responsiveness to partners' priorities.